Pyrolysis and reutilization of plant residues after phytoremediation of heavy metals contaminated sediments: For heavy metals stabilization and dye adsorption. (April 2018) - Gong, Xiaomin; Huang, Danlian; Liu, Yunguo; Zeng, Guangming; Wang, Rongzhong; Wei, Jingjing; Huang, Chao; Xu, Piao; Wan, Jia; Zhang, Chen
Graphical abstract: Highlights: Pyrolysis was applied to dispose plant residues obtained after phytoremediation. Heavy metals could be stabilized in plant residues after pyrolysis. Plant residues obtained after phytoremediation can be converted into biochar. The generated biochar could be used as an effective sorbent for dye adsorption. Abstract: This study aimed to investigate the effect of pyrolysis on the stabilization of heavy metals in plant residues obtained after phytoremediation. Ramie residues, being collected after phytoremediation of metal contaminated sediments, were pyrolyzed at different temperatures (300–700 °C). Results indicated that pyrolysis was effective in the stabilization of Cd, Cr, Zn, Cu, and Pb in ramie residues by converting the acid-soluble fraction of metals into residual form and decreasing the TCLP-leachable metal contents. Meanwhile, the reutilization potential of using the pyrolysis products generated from ramie residues obtained after phytoremediation as sorbents was investigated. Adsorption experiments results revealed that the pyrolysis products presented excellent ability to adsorb methylene blue (MB) with a maximum adsorption capacity of 259.27 mg/g. This study demonstrated that pyrolysis could be used as an efficient alternative method for stabilizing heavy metals in plant residues obtained after phytoremediation, and their pyrolysis products could be reutilized for dye adsorption.